Case of lipoatrophic diabetes induced by juvenile dermatomyositis. Issue 3 (1st December 2017) - Baba, Yusuke; Kaneko, Hiyori; Takemoto, Minoru; Ide, Kana; Haga, Yuki; Kanda, Tatsuo; Akita, Shinsuke; Kubota, Yoshitaka; Kuroda, Masayuki; Kitagawa, Yutaka; Yokote, Koutaro
Abstract: Lipodystrophy is a rare condition that is often accompanied by one or more metabolic diseases. Here, we report a case of lipoatrophic diabetes induced by juvenile dermatomyositis. Although pioglitazone was not effective for lowering blood glucose levels, our observation suggested that it improved liver function slightly. The effectiveness of metreleptin for lowering blood glucose levels could not be determined, as we administered it in a short period. Liver biopsy showed burned‐out non‐alcoholic steatohepatitis. The present results show that the successful treatment of lipoatrophic diabetes induced by juvenile dermatomyositis requires an early diagnosis and therapeutic intervention. Abstract : A case of lipoatrophic diabetes induced by juvenile dermatomyositis.